The state of art: social constructionism and the therapeutic performance in Brazil - Fernandes, Taffarel Ramires (2019)
The present review intended to propose the mapping of scientific articles that refer to the Social Constructionist psychotherapeutic clinic. From the bibliographic method called "State of art", a survey on scientific articles, published in the virtual platforms Biblioteca Virtual de Saúde – Psicologia (BVS-PSI) and Scientific Electronic Library Online (SciELO), was carried out. As a result, 09 articles were collected, which after been read in full, were organized into 03 thematic axes: theoretical approaches, narratives about the therapist and the concept of self. This study process evidenced the orientation of social constructionism to the constitution of a collaborative clinical practice in which the therapist acts in a reflexive, dialogic and engaged way.